CHALLENGES FACED BY AUDITORS WHEN ESTIMATING FAIR VALUES. AN EXPERIMENT IN AN EMERGING ECONOMY - DEACONU, Adela; CIURDAȘ, Ioana; BONACI, Carmen (Studia Universitatis Babeș-Bolyai Oeconomica, 2021)
Risks related to fair value (FV) estimates and their impact on the audit process represent a crucial topic in accounting and audit literature. Therefore, this paper focuses on one of the influential factors of FV estimation and related risks in audit missions, i.e. the valuation process performed (provider and measurement). In doing so, it addressees a less analysed FV level of estimation – level 3 according to IFRS 13, ’the models’, for the case of tangible assets. An experiment is conducted on a group of auditors, members of the Romanian audit professional body. The results reveal that, if the internal control quality is high, auditors differentiate between FV providers in the case of: FV measurement, i.e. income valuation approach versus cost approach, which implies additional effort for verification and risk of misstatement, when the estimation is provided by a third party instead of management. These findings could be related to the volatility of the investigated economic context and the respondents’ level of knowledge and expertise. We infer that respondents have a moderate understanding of valuation logic and methodology while excessively relying on their own valuator. JEL classification: M41, M42, R32, G12.